Combinational Pretreatment of Colony-Stimulating Factor 1 Receptor Inhibitor and Triptolide Upregulates BDNF-Akt and Autophagic Pathways to Improve Cerebral Ischemia - Xiaoxue Du; Feng Gao; Shijia Chen; Benson O. A. Botchway; Nashwa Amin; Zhiying Hu; Marong Fang (Mediators of Inflammation)
Ki20227, a selective inhibitor of colony-stimulating factor 1 receptor (CSF1R), has been suggested to regulate microglia inflammatory function and neuronal synaptic plasticity. Triptolide (TP) pretreatment has neuroprotective effects through its anti-inflammatory and antiapoptotic features in ischemic stroke mice. However, the underlying mechanism and pathway are presently unclear. We thus investigated the association between neuroprotective effects of combined TP and Ki20227 and BDNF-Akt and autophagy pathways. Ki20227 was administrated for 7 days, and TP was administered once 24 hours prior to building the ischemic stroke model in C57BL/6 mice. Behavioral tests, Golgi staining, immunofluorescence, and western blot analyses were employed to examine neuroprotective effects of TP and Ki20227. TP and Ki20227 pretreatments improved the neurobehavioral function in stroke mice. Synaptic protein expressions and density of dendritic spine density were upregulated in Ki20227 and TP pretreated stroke mice. Further, optimized integration of TP and Ki20227 pretreatments upregulated the NeuN expression and downregulated Iba1 expression after stroke. In addition, both TP and Ki20227 pretreatments significantly upregulated BDNF, p-Akt/Akt, and Erk1/2 protein expressions and autophagy related proteins (LC3II/I, Atg5, and p62), indicating the activation of BDNF and autophagic pathways. Optimized integration of TP and Ki20227 can improve cerebral ischemia by inhibiting CSF1R signal and trigger autophagy and BDNF-Akt signaling pathways to increase dendritic spine density and synaptic protein expressions, which in turn enhances neurobehavioral function.